COMMUNITY DEVELOPMENT STRATEGY THROUGH IDENTIFICATION OF TANGIBLE AND INTANGIBLE ASSETS FOR THE DEVELOPMENT OF BARAN BURING TOURISM KAMPUNG - Ema Yunita Titisari; Julaihi Wahid; Damayanti Asikin; Herlindah Herlindah; Heptari Elita Dewi (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
Suburban areas often experience development pressures, with implications for changing green space into built areas, rural cultures into urban ones, and poverty into prosperity. The development of Buring Kampong (suburban settlement) in Malang City into a tourism kampong, in addition to improving the local economy, must also be able to support environmental quality and community independence. This research used the Asset Based Community Development (ABCD) approach in identifying tangible and intangible assets. The data were collected through field observation, focused group discussion, interviews, and secondary data. Tangible aspects include land use, natural and artificial resources, infrastructure, accessibility, machinery and equipment, and local architecture. Meanwhile, intangible assets include intellectual property, potential branding development, goodwill, software/web, formal and informal organization, social and cultural values, and potential customers. The data obtained were presented descriptively and discussed together, as a triangulation process. The results showed the diversity and breadth of tangible and intangible assets of Baran village, and both of these assets can be directly found in the field and during FGDs and interviews. This research is also an effort to strengthen community engagement and public awareness about their assets, and this activity needs to be continuously improved, to have a better level of community engagement, confidence, social participation, branding, and networking.